2014
DOI: 10.1089/jir.2013.0043
|View full text |Cite
|
Sign up to set email alerts
|

Effect of IL-12B, IL-2, TGF-β1, and IL-4 Polymorphism and Expression on Hepatitis B Progression

Abstract: The hepatitis B virus (HBV) infection-induced chronic inflammation is considered to be the major etiological factor for HBV-related disease chronicity. Cytokines act as the key coordinators of the inflammatory responses involved in HBV disease pathogenesis. The present study assessed association among IL-12B(+1188), IL-2(-330), TGF-β1(-509), and IL-4(-590) genotypes; mRNA; and protein levels with HBV-hepatocellular carcinoma (HCC) risk in India. For this, 403 subjects (153 controls, 67 inactive HBV-carriers, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 42 publications
1
36
0
1
Order By: Relevance
“…There were 1,427 HCC cases and 3,735 controls, and all studies were hospital-based. In studies by Falleti et al [14], Qi et al [15], Radwan et al [16], Xin et al [17], and Shi et al [18], the control genotype distributions were in Hardy-Weinberg equilibrium, but they were not in the studies by Saxena et al [19] and Ma et al [20]. In the Kim et al study [13], it could not be determined whether the genotype distribution of the controls was in Hardy-Weinberg equilibrium because the TT and CT genotypes were counted as a single group.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…There were 1,427 HCC cases and 3,735 controls, and all studies were hospital-based. In studies by Falleti et al [14], Qi et al [15], Radwan et al [16], Xin et al [17], and Shi et al [18], the control genotype distributions were in Hardy-Weinberg equilibrium, but they were not in the studies by Saxena et al [19] and Ma et al [20]. In the Kim et al study [13], it could not be determined whether the genotype distribution of the controls was in Hardy-Weinberg equilibrium because the TT and CT genotypes were counted as a single group.…”
Section: Resultsmentioning
confidence: 96%
“…Although most previous meta-analyses have reported negative results for this association, the results of primary studies seem to suggest some tendencies, in terms of the infecting hepatitis virus. Of the four studies including HBV-infected subjects, three indicated a significant association between TGF-β1 C-509T variants and decreased HCC susceptibility [13,15,17,19]. However, two studies using HCV-infected subjects suggested a significant association between TGF-β1 C-509T variants and increased HCC susceptibility [16,20].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Among the remaining 69 articles, 31 studies, containing 10749 cancer patients and 11921 control subjects, were finally included in the present meta-analysis (Howell, et al, 2003;Amirzargar, et al, 2005;García-González, et al, 2007;Hou, et al, 2007;Lee, et al, 2007;Crusius, et al, 2008;Han, et al, 2008;Chen, et al, 2009;Miteva, et al, 2009;Tamandani, et al, 2009;Wei, et al, 2009;Zhao, et al, 2009;Wu, et al, 2009;Ben, et al, 2011;Liu, et al, 2011;Welsh, et al, 2011;Yang, et al, 2011;do CarmoVasconcelosde Carvalho V, et al, 2012;Huang, et al, 2012;Kaarvatn, et al, 2012;Roszak, et al, 2012;Sima, et al, 2012;Tao, et al, 2012;Jaiswal, et al, 2013;Sun, et al, 2013;Wang, et al,2013;Saxena, et al,2014;Jafarzadeh, et al,2015;Sun, et al,2015;Winchester, et al,2015;Yin, et al,2015)(see Fig. 1).…”
Section: Included Studiesmentioning
confidence: 99%
“…(27) Graves hastalığı olan kişilerde IL-2 GG genotip sıklığını kontrol grubuna göre anlamlı düzeyde daha yüksek bulmuşlar ve bu hastalarda IL-2 gen ifadesinin arttığını bildirmişlerdir. İran'da yapılan bir başka çalışmada da multiple sklerozlu hastalarda IL-2 -330 T alleline sahip kişilerin hastalığa karşı daha duyarlı olduğu belirlenmiştir (28 (34). Ülkemizde ise hepatit B ve C hastalığı ile IL-2 -330 polimorfizmi arasındaki ilişkiyi araştıran herhangi bir çalışmaya rastlanılmamıştır.…”
Section: Discussionunclassified